Modified Protocol for Establishment of Intracranial Arterial Dolichoectasia Model by Injection of Elastase Into Cerebellomedullary Cistern in Mice - Liu, Fei Xiang; Niu, Yu Ge; Zhang, Dao Pei; Zhang, Huai Liang; Zhang, Zhen Qiang; Sun, Rui Qin; Zhang, Yun Ke (Frontiers in Neurology, 2022)
Background and Purpose: This study aimed to construct an animal model of intracranial arterial dolichoectasia (IADE) applying the modified modeling protocol. Materials and Methods: 25 mu elastase and inactivated elastase were respectively injected into the cerebellomedullary cistern of sixty C57/BL6 mice which divived into experimental group and sham group. The modified modeling protocol clarified the brain three-dimensional parameters of mouse head fixation, angle of head inclination, fixed position of ear rod, needle holding technique, needle entry depth, prevention of liquid drug backflow, and storage conditions of elastase. The mortality, inflammatory factors, craniocerebral arteries scanning,vascular tortuosity index, artery diameter, pathology of the cerebrovascular were observed. Results: Within differently surveyed stage, the total mortality of mice in the experimental group was 20%. ELISA showed that the levels of matrix metalloproteinase-9 (MMP-9) and tumor necrosis factor α (TNF-α) in peripheral blood were increased significantly after modeling. Angiography showed that 100% of IADE in the experimental group were observed and the diameter and tortuosity index of the basilar artery were significantly increased (P< 0.01). EVG histological processing and staining showed that the internal elastic lamina was disrupted, the muscle layer was atrophied, and the connective tissue of the basilar artery was hyalinized with the vascular wall tunica media in the experimental group. Micro-computed tomography showed that the craniocerebral arteries of the mice in the experimental group were significantly elongated, tortuous, and dilated. Conclusion: The modified modeling protocol can reduce the mortality, improve the success rate and provide a stable animal model for IADE.